2022
DOI: 10.1038/s41598-022-07710-6
|View full text |Cite
|
Sign up to set email alerts
|

Long-term and daily use of molecular hydrogen induces reprogramming of liver metabolism in rats by modulating NADP/NADPH redox pathways

Abstract: Molecular hydrogen (H2) has emerged as a new therapeutic option in several diseases and is widely adopted by healthy people. However, molecular data to support therapeutic functions attributed to the biological activities of H2 remain elusive. Here, using transcriptomic and metabolomic approaches coupled with biochemistry and micro-CT technics, we evaluated the effect of long-term (6 months) and daily use of H2 on liver function. Rats exposed 2 h daily to H2 either by drinking HRW (H2 dissolved in H2O) or by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…On the one hand, H 2 can inhibit the damage of cellular DNA by ·OH and ONOO– to prevent cancer development; on the other hand, H 2 can remove ROS from cancer cells and inhibit multiple ROS-dependent metabolic signaling pathways to suppress cancer development. Studies have confirmed that H 2 can effectively reduce oxidative stress caused by various pathological conditions, including cancers, and promote the restoration of redox homeostasis (Adzavon et al 2022 ; Shi et al 2016 ; Kawai et al 2012 ).…”
Section: Anti-tumor Effect Of H 2 and The Underlyi...mentioning
confidence: 97%
See 1 more Smart Citation
“…On the one hand, H 2 can inhibit the damage of cellular DNA by ·OH and ONOO– to prevent cancer development; on the other hand, H 2 can remove ROS from cancer cells and inhibit multiple ROS-dependent metabolic signaling pathways to suppress cancer development. Studies have confirmed that H 2 can effectively reduce oxidative stress caused by various pathological conditions, including cancers, and promote the restoration of redox homeostasis (Adzavon et al 2022 ; Shi et al 2016 ; Kawai et al 2012 ).…”
Section: Anti-tumor Effect Of H 2 and The Underlyi...mentioning
confidence: 97%
“…4 ). H 2 , on the other hand, combats oxidative stress in various disease conditions and restores redox balance in the body’s environment by regulating the NADH/NADPH pathway (Adzavon et al 2022 ; Tao et al 2019 ), thereby safeguarding T cell activation and preventing apoptosis. Moreover, in this condition, compared with routine anti-tumor medicine, the high permeability of H 2 grants it to easily penetrate inside the tumor, even into structures such as the mitochondria of the TILs.…”
Section: Anti-tumor Effect Of H 2 and The Underlyi...mentioning
confidence: 99%
“…In studies performed on the model of aplastic anemia, it was shown that the use of H 2 influences mesenchymal stem cells, as it contributes to an increase in the number of colony-forming units [ 85 , 108 ]. In addition, the introduction of hydrogen positively modulates the state and functional activity of mitochondria in various cancer cells [ 109 ].…”
Section: The Effect Of Molecular Hydrogen On Various Cell Pools and R...mentioning
confidence: 99%
“…In addition, H 2 quickly penetrates several organelles, as well as the blood–brain barrier, and is non-toxic even at high concentrations. Moreover, it is used frequently to treat disorders linked to oxidative stress because of its ability to interfere with reactive oxygen species (ROS) in living systems [ 14 ]. On the other hand, some researchers note that H 2 decreases the delayed-onset muscle soreness after downhill running [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is used frequently to treat disorders linked to oxidative stress because of its ability to interfere with reactive oxygen species (ROS) in living systems [ 14 ]. On the other hand, some researchers note that H 2 decreases the delayed-onset muscle soreness after downhill running [ 14 ]. Some researchers have demonstrated that it improves the muscle function during exercise without having any negative impact on blood oxidative markers [ 15 ].…”
Section: Introductionmentioning
confidence: 99%